FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMINA TAHUN 2018 - 2020 - Yeniasari Rizkia Budi; Bella Barza Dewi (Institut Bisnis Muhammadiyah Bekasi, 2022)
The company of a business entity is a characteristic of a goal of economic activity, which has a long-term focus on sustaining life (going concern). Going concern audit opinion, audit opinion on a company's report if the financial statements experience different conditions from a financial business, then the company has problems in its performance. The purpose of this study was to determine the factors that influence the Going Concern Audit Opinion Partially and Simultaneously. The sampling technique used was the purposive sampling technique. The sample obtained was 40 companies from 75 companies in the basic and chemical industry sector listed on the Indonesia Stock Exchange in 2018-2020, so the data studied were found to be 120. The method used was logistic regression analysis with the help of SPSS 26. Based on the results of this study, partial and simultaneous partial Profitability, Liquidity, Company Growth, and the Previous Year's Audit Opinions have no effect on the acceptance of Going Concern Audit Opinions.